Physico-chemical characteristics of some soils from Mali and their potential in heavy metal removal - Sällström, Märit (SLU/Dept. of Soil and Environment, 2008)
Rivers, streams and groundwater contaminated by heavy metals is a growing concern world wide as the pressure on existing water resources is increasing. Unfortunately, low income countries are afflicted the most. There is a need for cost efficient and simple methods and techniques to solve the problem. Previous studies have indicated great potential for clay minerals in pollution control. However, the studies have been carried out on synthesized clays and through modeling predictions. The objective for this study was to investigate natural mixed clays from Mali and their potential in heavy metal removal.